Multi-layer coated silicon-based negative electrode material and preparation method and application thereof
Through the preparation method of multi-layer coated silicon-based anode material, the problems of short cycle life and poor conductivity of silicon-based anode material are solved, and longer cycle life and higher rate performance are achieved.
Patent Information
- Application Number
- CN202411931112.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-25
AI Technical Summary
The silicon-based anode material has a short cycle life in lithium-ion batteries, and volume expansion leads to degradation of mechanical and electrical pathways, unstable SEI layer, increasing polarization voltage, and degrading active materials.
The preparation method of multi-layer coated silicon-based negative electrode material is adopted. The mixed ball mill of micron silicon with lithium source and phosphate, heating constant temperature reaction, mixed ball mill with an annular structure organic sulfur source, and high-temperature calcination is carried out in the atmosphere of the combustion-assisted gas to form a Si@SiO2@LPO@C structure, reducing mechanical stress, ensuring particle integrity, and building mixed ionic and electronic conductive channels.
It extends the cycle life of the silicon negative electrode, reduces volume changes during charging and discharging, optimizes conductivity, improves rate performance and fast charging capabilities, and enhances the stability and cycle performance of the battery.
Smart Images

Figure CN119695125A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-ion batteries, and in particular relates to a multi-layer coated silicon-based negative electrode material and a preparation method and application thereof. Background Art
[0002] Silicon (Si) is considered one of the most promising anode materials for next-generation high-energy-density lithium-ion batteries (LIBs), mainly due to its high Si abundance and ultra-high theoretical capacity (3579 mAh / g, compared to 372 mAh / g for graphite). However, its significant volume change (~300%) during lithiation and delithiation can lead to degradation of mechanical and electrical pathways, ultimately resulting in a significant drop in capacity during cycling, which poses a severe challenge to the stable operation of the battery. In addition, due to repeated volume expansion, the newly exposed surface of Si reacts with the electrolyte, continuously forming SEI and causing rapid capacity decay.
[0003] Typically, liquid carbonate-based electrolyte interfaces show poor stability due to the loose structure and low modulus of the in-situ formed Li2CO3. The SEI layer has been shown to be electrochemically inert and electronically insulating, so a thick SEI not only degrades the active materials but also increases the polarization voltage. The mechanical structural degradation coupled with the unstable thick SEI layer leads to rapid capacity decay of silicon anodes.
[0004] To address these challenges, it is urgent to develop a multilayer-coated Si-based anode material that can help extend the cycle life of high-capacity Si anodes by designing a mechanically robust architecture and a stable Si SEI layer. Summary of the invention
[0005] Based on the defects of the prior art, the first purpose of the present invention is to provide a method for preparing a multi-layer coated silicon-based negative electrode material; the second purpose of the present invention is to provide a multi-layer coated silicon-based negative electrode material prepared by the preparation method; the third purpose of the present invention is to provide a negative electrode plate, which is prepared by using the multi-layer coated silicon-based negative electrode material of the present invention, and does not require the addition of additional conductive agent, thereby reducing the use of raw materials and reducing manufacturing costs; the fourth purpose of the present invention is to provide the use of the multi-layer coated silicon-based negative electrode material or the negative electrode plate in the preparation of lithium-ion batteries.
[0006] The purpose of the present invention is achieved through the following technical solutions:
[0007] In one aspect, the present invention provides a method for preparing a multi-layer coated silicon-based negative electrode material, the preparation method comprising the following steps:
[0008] Step 1, mixing micron silicon, lithium source and phosphate and ball milling to obtain a first mixture;
[0009] Step 2, heating the first mixture to react at a constant temperature to obtain a first product;
[0010] Step 3, mixing the first product with the organic sulfur source having a cyclic structure and performing ball milling to obtain a second mixture;
[0011] Step 4: calcining the second mixture at high temperature in a combustion-supporting gas atmosphere to obtain a second product, which is a multi-layer coated silicon-based negative electrode material.
[0012] The present invention proposes a "core-shell" structure that uses micron silicon to synthesize an outer layer while doping S elements through a solid phase synthesis method, and synthesizes a Si&S@SiO2@LPO@C structure on micron silicon. This design of SiO2 / LPO layer has been proven to reduce mechanical stress and ensure the particle integrity of micron silicon during the cycle. The SiO2@LPO@C structure of the Si outer layer doped with S, combined with electronic conductivity and a three-dimensional interconnected carbon coating framework, successfully constructs a mixed ion and electronic conductive channel that runs through the entire electrode; this channel improves the conductivity of the silicon negative electrode material and inhibits the expansion of the silicon negative electrode material.
[0013] In the above preparation method, preferably, in step 1, the lithium source is selected from a combination of one or more of lithium hydroxide, lithium carbonate, lithium nitrate, lithium chloride and lithium acetate; but not limited thereto.
[0014] In the above preparation method, preferably, in step 1, the phosphate is selected from a combination of one or more of diammonium dihydrogen phosphate, diammonium hydrogen phosphate and orthophosphoric acid; but not limited thereto.
[0015] In the above preparation method, preferably, in step 1, the molar ratio of the lithium source to the phosphate is 3:1 to 6:1.
[0016] In the above preparation method, preferably, in step 1, the molar ratio of the micron silicon to the lithium source is 0.5:1 to 1:1.
[0017] In the above preparation method, preferably, in step 1, the rotation speed of ball milling is 200 to 600 rpm / min; and the ball milling time is 1 to 4 h.
[0018] In the above preparation method, preferably, in step 2, the temperature for the heating constant temperature reaction is 300-800° C., and the constant temperature time is 0.5-2 h.
[0019] In the above preparation method, preferably, in step three, the organic sulfur source of the ring structure is selected from one or more combinations of sulfided polyacrylonitrile, sulfided polyacrylic acid, sulfided polystyrene, sulfided polypyrrole, sulfided polythiophene, sulfided carbon nanotubes and sulfided graphene; but not limited thereto.
[0020] In the above preparation method, preferably, in step three, the mass ratio of the first product to the organic sulfur source of the cyclic structure is 1:1 to 1:5.
[0021] In the above preparation method, preferably, in step three, the rotation speed of ball milling is 200 to 600 rpm / min; and the ball milling time is 2 to 6 hours.
[0022] In the above preparation method, preferably, in step 4, the combustion-supporting gas is an argon-hydrogen mixed gas, wherein the content of hydrogen is not less than 5%.
[0023] In the above preparation method, preferably, in step 4, the high temperature calcination temperature is 500-1000° C., and the calcination time is 1-4 hours.
[0024] In the above preparation method, preferably, the particle size of the micron silicon is 1 to 3 μm.
[0025] In the above preparation method, preferably, the micron silicon is dried before ball milling, the drying temperature is 50-70° C., and the drying time is 2-8 hours.
[0026] On the other hand, the present invention also provides a multi-layer coated silicon-based negative electrode material, which is prepared by the above-mentioned preparation method.
[0027] In another aspect, the present invention further provides a negative electrode sheet, and a method for preparing the negative electrode sheet comprises:
[0028] The multi-layer coated silicon-based negative electrode material according to claim 8 and sodium hydroxymethyl cellulose are mixed in an organic solvent to obtain a suspension, the suspension is dispersed and then coated on a copper foil, and dried to form a negative electrode sheet.
[0029] In the above-mentioned negative electrode plate, preferably, the mass ratio of the multi-layer coated silicon-based negative electrode material to the sodium hydroxymethyl cellulose is 5:1 to 10:1.
[0030] In the above-mentioned negative electrode sheet, preferably, the solid content in the suspension is 50% to 70%.
[0031] In the above-mentioned negative electrode sheet, preferably, the organic solvent is selected from N-methylpyrrolidone; but not limited thereto.
[0032] In the above-mentioned negative electrode sheet, preferably, the drying is carried out in an argon glove box, and the drying is first blast drying and then vacuum drying; the blast drying temperature is 80-110°C; the drying time is 0.5-3h; the vacuum drying temperature is 20-30°C, and the drying time is 1-4h.
[0033] On the other hand, the present invention also provides the use of the above-mentioned multi-layer coated silicon-based negative electrode material or the above-mentioned negative electrode plate in the preparation of a lithium-ion battery.
[0034] Beneficial effects of the present invention:
[0035] (1) In the preparation method of the multi-layer coated silicon-based negative electrode material of the present invention, the addition of S into silicon can control the volume expansion of the silicon negative electrode and design the outer coating structure layer, which can reduce the volume change during the charge and discharge process, thereby extending the service life of the battery; the introduction of sulfur element can also optimize the conductivity of the silicon-carbon negative electrode, reduce resistance, and improve the electron transfer efficiency, thereby improving the battery's rate performance and fast charging capability. Further addition of S can optimize the formation of the electrolyte interface film (SEI), reduce side reactions, and enhance the stability and cycle performance of the battery.
[0036] (2) The preparation method of the multi-layer coated silicon-based negative electrode material of the present invention is simple, and is carried out through a two-step reaction. Each step of the reaction process is simple and easy to operate, which has industrial advantages.
[0037] (3) The multi-layer coated silicon-based negative electrode material of the present invention has a multi-layer coating structure, the coating layer interface is uniform, and the thickness is controllable, which is helpful for the improvement of the silicon negative electrode; the Si surface is coated with a two-layer structure, the inner layer is coated with SiO2@Li3PO4 to improve its conductivity; the outer layer is coated with C@S, which helps ion deintercalation by creating a fast ion channel, and the doping of S atoms further expands the internal pores, which improves the kinetic performance while also effectively controlling the expansion.
[0038] (4) When the multi-layer coated silicon-based negative electrode material of the present invention is used to prepare the negative electrode plate, no additional conductive agent is required, which reduces the use of raw materials and reduces the manufacturing cost.
[0039] (5) The multi-layer coated silicon-based negative electrode material of the present invention has better rate performance and cycle stability.
[0040] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0042] Figure 1Schematic diagram of the reaction process for preparing multi-layer coated silicon-based anode material (Si@MC).
[0043] Figure 2 This is a scanning electron microscope microscopic morphology comparison image of the multilayer coated silicon-based negative electrode material (Si@MC) prepared in Example 1 of the present invention and the conventional pure μSi material of Comparative Example 1, and a transmission electron microscope image of the Si@MC material.
[0044] Figure 3 This is a comparison chart of the cycle performance and rate performance of the multi-layer coated silicon-based negative electrode material (Si@MC) prepared in Example 1 of the present invention and the conventional pure μSi material in Comparative Example 1. DETAILED DESCRIPTION
[0045] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. The process, conditions, reagents, experimental methods, etc. for implementing the present invention, except for the contents specifically mentioned below, are all common knowledge and common common sense in the art, and the present invention does not particularly limit the contents.
[0046] Embodiment 1:
[0047] This embodiment provides a multi-layer coated silicon-based negative electrode material (Si@MC) and a preparation method thereof, such as Figure 1 As shown, the preparation method comprises the following steps:
[0048] (1) Take 10 g of micron silicon powder (μSi, commercially available, Aladdin, product number S401567, particle size about 1-3 μm) and put it into a drying oven at 60° C. for 4 h to remove residual moisture on the surface.
[0049] (2) Weigh 5.8 g of dried micronized silicon powder, 5.0 g of lithium hydroxide and 24.0 g of ammonium dihydrogen phosphate into a ball mill, adjust the equipment speed to 400 rpm / min, and grind for 2 h to obtain a uniform mixture.
[0050] (3) The mixture in step (2) was placed in a microwave heater and heated to 550° C., and then the heating was stopped. The mixture was then kept at 550° C. for 1 h, and then cooled and taken out as a sample, which was named Product 1.
[0051] (4) Weigh 10 g of product 1 and 10 g of sulfide polyacrylonitrile (SPAN) and put them into a ball mill for mixing. Adjust the equipment speed to 400 rpm / min and grind for 2 h to obtain a uniform mixture.
[0052] (5) The mixture in step (4) is placed in a high-temperature furnace filled with argon-hydrogen mixed gas (hydrogen content 5%) and calcined at a temperature of 800° C. for 2 h to obtain the target product, a multilayer-coated silicon-based negative electrode material, named Si@MC.
[0053] Figure 1 Schematic diagram of the reaction process for preparing multilayer coated silicon-based negative electrode materials (Si@MC). (a) in the figure is a schematic diagram of the formation of SiO2 and Li3PO4 sheets on the surface of product 1, μSi; when μSi is heated, the Si on its surface will undergo an oxidation reaction with oxygen in the air, forming a layer of SiO2 sheets on the surface, and further LiOH and NH4H2PO4 will react with Li3PO4 when heated. When heating continues, Li3PO4 will sinter on the surface of the SiO2 sheets. (b) in the figure is a schematic diagram of the reaction of product 1 and SPAN; in an inert gas atmosphere, product 1 and SPAN are rapidly sintered on the surface of product 1 under the action of the combustion-supporting gas H2, and the S therein will be embedded in the carbon layer, expanding the crystal structure of the carbon layer and improving the kinetic performance.
[0054] This embodiment also provides a method for preparing a Si@MC electrode sheet using the multi-layer coated silicon-based negative electrode material (Si@MC) prepared above. The negative electrode sheet does not need to add a conductive agent. The preparation method is as follows:
[0055] A total of 10 g of multilayer coated silicon-based negative electrode material (Si@MC) and sodium carboxymethyl cellulose (CMC) were weighed in a mass ratio of 9:1, and N-methylpyrrolidone (NMP) was added for dispersion and the solid content was adjusted to 60%; then, the mixture was dispersed at 600 rpm for 5 min and the speed was adjusted to 2000 rpm for high-speed dispersion for 30 min to obtain a mixed slurry, which was then coated on a copper foil; the coated sample was placed in a 110°C blast oven and dried for 2 h, then taken out, and then dried in a vacuum dryer for 1 h and cut into 12 mm small discs, namely: Si@MC pole pieces, which were used as negative electrodes.
[0056] This embodiment also provides a lithium-ion button battery, and the assembly process is as follows:
[0057] The button battery was assembled in an argon glove box (with water content <1ppm and oxygen content <1ppm), with the Si@MC electrode as the negative electrode and the lithium sheet as the positive electrode. 1M LiPF6 electrolyte of ethylene carbonate and diethyl carbonate (volume ratio: EC:DEC=1:1) was added during the assembly process. After the button battery was assembled, it was placed in an oven at 25°C for activation for 12 hours and then taken out for testing.
[0058] Comparative Example 1:
[0059] As a comparative example, pure micron silicon powder (μSi, commercially available, Aladdin, item number S401567, particle size of about 1-3 μm) was used to prepare the negative electrode sheet and assemble the buckle. Specifically:
[0060] Negative electrode sheet preparation:
[0061] Weigh 10g of pure micron silicon powder (μSi), conductive carbon black (SP) and sodium carboxymethyl cellulose (CMC) in a mass ratio of 4:5:1, add NMP to disperse and adjust the solid content to 60%; then disperse at 600rpm for 5min and adjust the speed to 2000rpm for high-speed dispersion for 30min to obtain a mixed slurry, which is then coated on copper foil. The coated sample is placed in a 110℃ blast oven and dried for 2h, then taken out, and then dried in a vacuum dryer for 1h and cut into 12mm small discs, namely: μSi pole pieces, as negative electrodes for standby use.
[0062] Lithium-ion button battery assembly:
[0063] The button battery was assembled in an argon glove box (with water content <1ppm and oxygen content <1ppm), with the μSi electrode as the negative electrode and the lithium sheet as the positive electrode. 1M LiPF6 electrolyte of ethylene carbonate and diethyl carbonate (volume ratio: EC:DEC=1:1) was added during the assembly process. After the button battery was assembled, it was placed in an oven at 25°C for activation for 12 hours and then taken out for testing.
[0064] Test experiment:
[0065] The lithium ion button batteries prepared in Example 1 of the present invention and Comparative Example 1 were tested for button battery performance, and the specific test process is as follows:
[0066] Let stand for 2h→discharge rate 0.1C, voltage ≤0.005v→constant current discharge 0.05mA, voltage ≤0.005v→constant current discharge 0.02mA, voltage ≤0.005v→let stand for 10min→charge rate 0.1C, voltage ≥2V.
[0067] Test results such as Figure 2 and Figure 3 shown.
[0068] Figure 2 The scanning electron microscope microscopic morphology comparison diagram of the multilayer coated silicon-based negative electrode material (Si@MC) prepared in Example 1 of the present invention and the conventional pure μSi material of Comparative Example 1 and the transmission electron microscope diagram of the Si@MC material; Figure 2 (a) is a scanning electron microscope microscopic image of pure μSi material; Figure 2 (b) is the scanning electron microscope microscopic morphology of Si@MC material; Figure 2 (c) in the figure is a transmission electron microscope image of Si@MC material.
[0069] Depend on Figure 2 It can be seen that: from Figure 2 In (a), it can be seen that the pure μSi material is a single particle of about 1 to 2 μm, and its outer surface is relatively smooth. Other substances are adhered to the surface of the Si@MC material. It can be further seen from the TEM image that there are lamellae of about 12 to 25 nm on the periphery, which is the lamellae structure designed in the target product.
[0070] Figure 3 This is a comparison chart of the cycle performance and rate performance of the multi-layer coated silicon-based negative electrode material (Si@MC) prepared in Example 1 of the present invention and the conventional pure μSi material in Comparative Example 1. Figure 3 (a) is a comparison of the capacity curves of μSi material and Si@MC material at 0.2C; Figure 3 (b) is a comparison of the capacity curves of μSi material and Si@MC material at different rates.
[0071] Depend on Figure 3 It can be seen that: from (a) in the figure, it can be seen that the Si@MC material can reach a discharge capacity of 2402mAh / g, and its first efficiency can reach 96.1%, while the discharge capacity of the μSi material is only 1567mAh / g, and its first efficiency is only 90.8%, indicating that the Si@MC material prepared in Example 1 of the present invention can improve its capacity, and the outer layer coating reduces side reactions, and the first efficiency is higher. From (b) in the figure, it can be seen that with the increase of the rate, both the μSi material and the Si@MC material show a decline in performance, mainly due to their kinetic factors, but the Si@MC material has obvious advantages over the μSi material. At the same rate, the Si@MC material is far superior to the μSi material. At the 5C rate, the Si@MC has a capacity of 1543mAh / g, while the μSi material has a capacity of only 562mAh / g.
[0072] The present invention uses specific embodiments to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. A method for preparing a multi-layer coated silicon-based negative electrode material, characterized in that: The preparation method comprises the following steps: Step 1, mixing micron silicon, lithium source and phosphate and ball milling to obtain a first mixture; Step 2, heating the first mixture to react at a constant temperature to obtain a first product; Step 3, mixing the first product with the organic sulfur source having a cyclic structure and performing ball milling to obtain a second mixture; Step 4: calcining the second mixture at high temperature in a combustion-supporting gas atmosphere to obtain a second product, which is a multi-layer coated silicon-based negative electrode material.
2. The preparation method according to claim 1, characterized in that: In step 1, the lithium source is selected from a combination of one or more of lithium hydroxide, lithium carbonate, lithium nitrate, lithium chloride and lithium acetate; Preferably, the phosphate is selected from a combination of one or more of diammonium phosphate, diammonium hydrogen phosphate and orthophosphoric acid.
3. The preparation method according to any one of claims 1 or 2, characterized in that: In step 1, the molar ratio of the lithium source to the phosphate is 3:1 to 6:1; Preferably, the molar ratio of the micron silicon to the lithium source is 0.5:1 to 1:1; Preferably, the ball milling speed is 200-600 rpm / min; and the ball milling time is 1-4 h.
4. The preparation method according to claim 1, characterized in that: In step 2, the temperature for heating and isothermal reaction is 300-800° C., and the isothermal time is 0.5-2 h.
5. The preparation method according to claim 1, characterized in that: In step 3, the organic sulfur source of the ring structure is selected from one or more combinations of sulfided polyacrylonitrile, sulfided polyacrylic acid, sulfided polystyrene, sulfided polypyrrole, sulfided polythiophene, sulfided carbon nanotubes and sulfided graphene; Preferably, the mass ratio of the first product to the organic sulfur source of the cyclic structure is 1:1 to 1:5; Preferably, the ball milling speed is 200 to 600 rpm / min; and the ball milling time is 2 to 6 hours.
6. The preparation method according to claim 1, characterized in that: In step 4, the combustion-supporting gas is a mixed gas of argon and hydrogen, wherein the content of hydrogen is not less than 5%; Preferably, the high temperature calcination temperature is 500-1000° C., and the calcination time is 1-4 hours.
7. The preparation method according to claim 1, characterized in that: The particle size of the micron silicon is 1 to 3 μm; Preferably, the micron silicon is dried before ball milling, the drying temperature is 50-70° C., and the drying time is 2-8 hours.
8. A multi-layer coated silicon-based negative electrode material, which is prepared by the preparation method according to any one of claims 1 to 7.
9. A negative electrode plate, characterized in that: The method for preparing the negative electrode plate comprises: The multi-layer coated silicon-based negative electrode material according to claim 8 and sodium hydroxymethyl cellulose are mixed in an organic solvent to obtain a suspension, the suspension is dispersed and then coated on a copper foil, and dried to form a negative electrode sheet; Preferably, the mass ratio of the multi-layer coated silicon-based negative electrode material to the sodium hydroxymethyl cellulose is 5:1 to 10:1; Preferably, the solid content of the suspension is 50% to 70%; Preferably, the organic solvent is selected from N-methylpyrrolidone; Preferably, the drying is carried out in an argon glove box, and the drying is first performed by blast drying and then by vacuum drying; the blast drying temperature is 80-110° C. and the drying time is 0.5-3 h; the vacuum drying temperature is 20-30° C. and the drying time is 1-4 h.
10. Use of the multi-layer coated silicon-based negative electrode material prepared by the preparation method according to any one of claims 1 to 7 or the multi-layer coated silicon-based negative electrode material according to claim 8 or the negative electrode plate according to claim 9 in the preparation of lithium-ion batteries.